Morphometric study of the atlantooccipital and the lateral atlantoaxial joints in small breed dogs with and without atlantoaxial instability - Pack, Felix; Hungerbühler, Valerie; Planchamp, Bastien; Forterre, Franck; Precht, Christina (Frontiers in Veterinary Science, 2026)
IntroductionThe combination of atlantoaxial instability (AAI) with several abnormalities and malformations of the craniovertebral junction in small breed dogs has been described, however there is limited knowledge regarding morphometric alterations of the synovial joints in this region. This study aimed to evaluate the morphometric differences of the lateral atlantoaxial and the atlantooccipital joints between dogs with and without AAI using computed tomography (CT) scans.Materials and methodsThis retrospective observational case–control study analyzed multiplanar reconstructed CT scans of 33 small and toy breed dogs (11 with AAI and 22 controls without AAI). The depth-to-length ratios of the articular surfaces of the atlantooccipital and lateral atlantoaxial joints were measured in dorsal and sagittal reconstructions and tested for significant differences between AAI and control groups.ResultsThe depth-to-length ratio of the occipital condyles in sagittal (p < 0.001) and dorsal planes (p < 0.007), as well as the facies articularis cranialis of the atlas in sagittal plane (p < 0.001), were significantly smaller in the AAI group, indicating that the occipital condyle and the cranial articular surface of the atlas were more shallow in the AAI group compared to the control group. The depth-to-length ratios of the lateral atlantoaxial joint surfaces were generally lower than those of the atlantooccipital joint, consistent with a flatter joint conformation, and some differences between AAI and control dogs were detected; however, these patterns were not consistent across planes.Discussion and conclusionThe atlantooccipital joint surfaces were more shallow in small breed dogs with AAI compared to controls. These results suggest that a certain degree of atlantooccipital joint dysplasia may be more commonly present in dogs with AAI, whereas morphometric alterations of the lateral atlantoaxial joints appear more complex and less consistently differentiated between groups.